3D Printing Quasi‐Solid‐State Asymmetric Micro‐Supercapacitors with Ultrahigh Areal Energy Density. Issue 20 (14th April 2018) - Shen, Kai; Ding, Junwei; Yang, Shubin
Abstract: A 3D printing approach is first developed to fabricate quasi‐solid‐state asymmetric micro‐supercapacitors to simultaneously realize the efficient patterning and ultrahigh areal energy density. Typically, cathode, anode, and electrolyte inks with high viscosities and shear‐thinning rheological behaviors are first prepared and 3D printed individually on the substrates. The 3D printed asymmetric micro‐supercapacitor with interdigitated electrodes exhibits excellent structural integrity, a large areal mass loading of 3.1 mg cm −2, and a wide electrochemical potential window of 1.6 V. Consequently, this 3D printed asymmetric micro‐supercapacitor displays an ultrahigh areal capacitance of 207.9 mF cm −2 . More importantly, an areal energy density of 73.9 µWh cm −2 is obtained, superior to most reported interdigitated micro‐supercapacitors. It is believed that the efficient 3D printing strategy can be used to construct various asymmetric micro‐supercapacitors to promote the integration in on‐chip energy storage systems. Abstract : A three‐dimensional (3D) printing approach was developed to fabricate quasi‐solid‐state asymmetric microsupercapacitors. With a high mass loading of 3.1 mg cm −2 and a wide voltage window of 1.6 V, the microsupercapacitor exhibits an ultrahigh areal energy density of 73.9 µWh cm −2 . Such an efficient strategy to construct asymmetric microsupercapacitors will promote the integration in on‐chip energy storage systems.